2010
DOI: 10.1007/s00330-010-1795-6
|View full text |Cite
|
Sign up to set email alerts
|

Can quantitative dynamic contrast-enhanced MRI independently characterize an ovarian mass?

Abstract: Threshold criteria established in this preliminary study using quantitative DCE-MRI provide an accurate method for the prediction of malignancy, particularly in preoperative indeterminate cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
36
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 27 publications
5
36
1
Order By: Relevance
“…Our previous preliminary study suggested the potential of using threshold criteria based on maximum tumour signal intensity (SI max ) and maximum tumour/psoas muscle signal intensity ratio (SI max ratio) [25]. In the present study, analysing a larger population, we have confirmed that these parameters are significantly different in benign and borderline/invasive malignant groups.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our previous preliminary study suggested the potential of using threshold criteria based on maximum tumour signal intensity (SI max ) and maximum tumour/psoas muscle signal intensity ratio (SI max ratio) [25]. In the present study, analysing a larger population, we have confirmed that these parameters are significantly different in benign and borderline/invasive malignant groups.…”
Section: Discussionsupporting
confidence: 90%
“…Studies have postulated a relationship between early enhancement of solid tumour components and malignancy [4,23,24] and a correlation with tumour angiogenesis biomarkers [2]. A preliminary study performed at our institution supports the use of threshold criteria based on the semi-quantitative evaluation of early tumour enhancement as an independent predictor of malignancy in a complex ovarian mass [25].…”
Section: Introductionmentioning
confidence: 92%
“…Two European centres have done pioneering work on DCE MRI of complex adnexal lesions [1520]. It is well known that factors related to tumour biological processes, such as VEGFR-2 expression and pericyte coverage index (PCI), are related to maximum uptake of gadolinium by the tumour [18].…”
Section: New Imaging Techniquesmentioning
confidence: 99%
“…Using semi-quantitative multiphase contrast-enhanced MRI, the predominant finding by both groups was that in adnexal masses where solid components demonstrate a rapid rate and high level of enhancement, there is a very high likelihood of malignancy, whereas a slow rate and low level of enhancement is associated with a high likelihood of a benign lesion [1517, 20]. …”
Section: New Imaging Techniquesmentioning
confidence: 99%
“…Time-intensity curves and descriptive DCE parameters of their enhancing solid components have aided differentiation of benign from borderline/ malignant lesions. [1][2][3][4][5][6] However, semi-quantitative assessment of DCE, which is based on signal enhancement, is altered by cardiac flow rate, arterial blood pressure and contrast agent dose. To overcome this, internal references have been suggested to provide lesion-to-internal (lesion-internal reference) ratios.…”
mentioning
confidence: 99%